2020
DOI: 10.18093/0869-0189-2020-30-5-609-628
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and children

Abstract: In December 2019, the world became aware of an epidemic of a very severe infection caused by a new coronavirus. Later, WHO declared a pandemic. The pediatricians were ready for the worst. The novel infection was expected to promptly spread among the most vulnerable population, children. But the clinicians soon understood that the situation is unbelievable: adults develop severe disease and die, while the children remain almost excluded from the infection spreading. 9 months have passed in the “new reality”. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 115 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…For example, children rarely have such clinical symptoms as rhinorrhea, wheezing, and general malaise. However, diarrhea in pediatric patients with COVID-19 infection is more common than in adults [24][25][26].…”
Section: Clinical Manifestations Risk Factors and Features Of The Cou...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children rarely have such clinical symptoms as rhinorrhea, wheezing, and general malaise. However, diarrhea in pediatric patients with COVID-19 infection is more common than in adults [24][25][26].…”
Section: Clinical Manifestations Risk Factors and Features Of The Cou...mentioning
confidence: 99%
“…Against the background of the absence of other symptoms of the disease in children in Spain and the USA, cases of soreness of the fingers or individual phalanges with signs of cutaneous vasculitis, superficially similar to frostbite, have been described. In May 2020, new publications appeared on the presence of this sign in Italy and Spain, and systematic data in the USA allow this symptom to be recommended as pathognomonic for the diagnosis of COVID-19 in children, even in laboratory-unconfirmed cases [24,27,28].…”
Section: Clinical Manifestations Risk Factors and Features Of The Cou...mentioning
confidence: 99%
“…Consequently, less attention is being paid to pediatric patients due to the milder course of the virus. Previous research has confirmed that the risk of developing severe and critical conditions in children is much lower than that in adults [ 8 ]. However, there is a concern that the number of tests will be reduced; consequently, the number of infected children and adolescents will be lower than the actual number.…”
Section: Introductionmentioning
confidence: 99%